Nacimos luchando! Crecimos en la victoria! Seguimos combatiendo al enemigo! en el V aniversario de los C.D.S. : …ojos y oídos de la revolución! (CDS (Comite de Defensa Sandinista))
Logo of the CDS repeated 5 times, on top of each other, as if coming from the distance and approaching the reader; blue background Poster advertising 5th year since the formation of the CDS in Nicaragua PO-0185